2019
DOI: 10.1016/j.apgeochem.2019.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Origin, distribution, and behaviour of rare earth elements in river bed sediments from a carbonate semi-arid basin (Tafna River, Algeria)

Abstract: A B S T R A C TThe behaviour and sources of rare earth elements (REE) in river sediments were investigated at ten stations and two dams of the Tafna basin (Northern Algeria) during contrasting hydrological conditions and using a combination of normalisation procedures, REE anomalies, various REE ratios, and multivariate statistical analysis. The ranking and REE concentrations were in the range of other carbonated areas. The classical fractionation of the heavy REE(HREE) erosion pattern, evidenced from upstream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 117 publications
0
9
0
2
Order By: Relevance
“…Moreover, in Ostrowite Lake and additionally in Kocioł, Kacze Oko and Rybie Oko a negative anomaly of Yb and Tm was observed respectively. The formulas presented by Benabdelkader et al 65 were used to confirm the above observations. It was assumed that the computations of Eu, Gd, Yb and Tm anomalies will have values above > 1.1 or below < 0.9, which indicates the occurrence of positive and negative anomalies, respectively.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…Moreover, in Ostrowite Lake and additionally in Kocioł, Kacze Oko and Rybie Oko a negative anomaly of Yb and Tm was observed respectively. The formulas presented by Benabdelkader et al 65 were used to confirm the above observations. It was assumed that the computations of Eu, Gd, Yb and Tm anomalies will have values above > 1.1 or below < 0.9, which indicates the occurrence of positive and negative anomalies, respectively.…”
Section: Resultsmentioning
confidence: 73%
“…This is confirmed by earlier studies by Sojka et al 32 , obtained for Lake Wadąg located in north-eastern Poland. Benabdelkader et al 65 demonstrated that reservoirs play an important role in REE retention (LREE) and to delay the release of MREE and HREE downstream. There was slightly more MREE in the individual lakes than HREE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Na verdade, eles são conhecidos por sua afinidade às frações finas em solos e sedimentos e pelas associações com várias frações químicas. Carbonatos, óxidos de ferro e matéria orgânica estão entre os fatores de controle mais importantes dos ETR (BENABDELKADER et al, 2019).…”
Section: Elementos Terras Raras (Etr)unclassified
“…O crescente uso médico dos ETR nas últimas décadas, juntamente com suas aplicações de alta tecnologia, demonstram a necessidade urgente de investigações sobre esses elementos. (BENABDELKADER et al, 2019;TANSEL, 2017 (SIGRH, 2004b).…”
Section: Elementos Terras Raras (Etr)unclassified